Caustic esophageal injury in clinical settings - Zuleika, Puspa; Saleh, Irsan; Murti, Krisna; Liberty, Iche Andriyani (Oto Rhino Laryngologica Indonesiana, 2023)
Background: esophageal stricture is loss of esophageal lumen patency and may involve injuries after ingesting caustic substances. This systematic review aims to review clinical presentations, diagnostic modalities involved, treatments and outcomes, and complications of esophageal strictures following caustic injuries.Methods: this systematic review involves original researches conducted between 2002-2022 indexed in PubMed and EuropePMC searched using following MeSH terms: “((caustic injury) OR (caustic burn)) AND (ingestion) AND (inflammation)” following PRISMA algorithm. Biases were assessed using STROBE checklist and presented as narratives.Results: searches yielded 326 results with 16 studies included in this review. Majority of caustic ingestion and strictures involved pediatric population due to accidental ingestion. Alkali ingestion has more severe presentation. Radiological imaging, including CT and MRI, may help in determining damages involved. Degrees of damages are related with mortalities or morbidities, and dilatation may improve quality-of-life in some cases.Conclusion: pediatric patients are at risk for accidental ingestions and alkali ingestion creates more severe damage. Radiological imaging may assist in determining involvement of underlying tissues.